Implikasi Keterlambatan Pembentukan Peraturan Pemerintah terhadap Undang-Undang - Abdul Malik Mahir Mustafa; Insan Tajali Nur; Rahmawati Al Hidayah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The untimely formation of government regulations on the delegation of laws is still a serious problem in the practice of forming laws and regulations in Indonesia. It was recorded that from 2021 to 2023 there were 16 government regulations that were formed late, which shows that there are problems in the follow-up mechanism for legislation delegations. The author analyzes whether the government has a legal obligation in the timeliness of the formation of government regulations as implementing rules. In addition, this study also examines the juridical and practical implications of the law if a delegated government regulation is formed late. The data used are quantitative and supported by doctrinal research methods through the analysis of laws and regulations, expert opinions, and related legal literature. The results of the study show that the government has a legal obligation to form government regulations in a timely manner. The delay in the formation of government regulations has an impact on disrupting the effectiveness of the implementation of the law and causes some provisions to not be implemented optimally because the implementing instruments are not yet available according to the specified deadline. In addition, these delays have the potential to cause legal uncertainty for the public, law enforcement officials, and policy implementing agencies. The vacuum of implementing rules can also trigger differences in interpretation, hinder policy implementation, and increase the risk of legal disputes. Therefore, this study emphasizes the importance of stricter monitoring and evaluation mechanisms against the deadline for the formation of government regulations to ensure legal certainty and regulatory effectiveness.